Exhaust gas purification catalyst
By sintering the BEA zeolite, structural defects are reduced, and the problem of insufficient HC adsorption capacity of the exhaust purification catalyst in the cold state is solved, and effective reduction of HC emissions in the cold area is achieved.
Patent Information
- Application Number
- CN202380059306.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-25
- Filing Date
- 2023-06-20
- Publication Date
- 2025-03-28
AI Technical Summary
In the cold state, the existing exhaust purification catalysts have insufficient HC adsorption capacity due to structural defects, which cannot effectively reduce HC emissions in the cold area.
By performing the firing treatment in BEA type zeolite, the firing temperature is controlled to be above 650°C and below 900°C to reduce structural defects, ensuring that the full half-maximum width of the diffraction peak with (A1+A2)/A0 value measured by FT-IR is less than 0.50 and the XRD is 2θ=22.5±0.1° is less than 0.30°.
The HC adsorption capacity of BEA type zeolite is improved, especially in the cold state, which significantly reduces the HC emissions in the cold area.
Smart Images

Figure BDA0005268818710000061 
Figure BDA0005268818710000071 
Figure BDA0005268818710000091
Abstract
Description
Technical Field
[0001] The present invention relates to an exhaust gas purification catalyst. Background Art
[0002] The exhaust gas from internal combustion engines such as automobile engines contains nitrogen oxides (NO x ), carbon monoxide (CO), hydrocarbons (HC), etc. These exhaust gases are purified by an exhaust purification catalyst device including an exhaust purification catalyst that oxidizes CO and HC and reduces NOx, and then discharged into the atmosphere.
[0003] Among them, regarding HC, it is difficult to purify HC by the catalyst when the catalyst is cold and has not yet warmed up, such as when the engine is started. Therefore, it has been practiced to include HC adsorbing materials in exhaust gas purification catalyst devices, which adsorb HC when it is cold and slowly release HC when it is warmed up, and then purify it by the catalyst.
[0004] For example, Patent Document 1 proposes a hydrocarbon adsorbent comprising: a BEA-type zeolite having a SiO2 / Al2O3 molar ratio (SAR) of less than 200, and a BEA-type zeolite having a SAR of 200 to 1000, and explains that by including the hydrocarbon adsorbent in an exhaust purification catalyst device, total hydrocarbon (THC) emissions can be reduced.
[0005] Prior art literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2007-275877 Summary of the invention
[0007] As proposed in Patent Document 1, it is believed that the use of BEA zeolite as a HC adsorbing material is effective for reducing HC emissions. However, BEA zeolite is prone to structural defects during synthesis. It is believed that in the structural defects of BEA zeolite, Si-O-Si bonds are cut to generate Si-OH groups. Since the Si-OH groups have a strong affinity for water, when BEA zeolite having structural defects is used as an exhaust purification catalyst, water is adsorbed to the Si-OH groups, thereby partially blocking the pores, and the expected HC adsorption capacity cannot be achieved.
[0008] Although the pore blockage caused by adsorbed water is eliminated when the catalyst becomes warm, the effect of adsorbed water is significantly manifested in the cold state, seriously hindering the reduction of HC emissions in the cold region.
[0009] The present invention has been accomplished in view of the above-mentioned circumstances.
[0010] An object of the present invention is to provide an exhaust gas purification catalyst having few structural defects, excellent HC adsorption capacity in a cold state, and capable of reducing HC emissions in a cold region.
[0011] The present invention is as follows.
[0012] [Scheme 1] An exhaust gas purification catalyst comprising BEA type zeolite,
[0013] In the FT-IR measurement using the BEA-type zeolite,
[0014] At 3730cm -1 Above and 3740cm -1 The following peak areas A1,
[0015] At 3720cm -1 Above and 3725cm -1 The following peaks have a peak area A2, and
[0016] In 1978cm -1 Above and 1983cm -1 The value of (A1+A2) / A0 calculated from the peak area A0 having the peak top is less than 0.50, and
[0017] The full width at half maximum of a diffraction peak at 2θ=22.5±0.1° in XRD measurement of the BEA-type zeolite is 0.30° or less.
[0018] [Scheme 2] According to the exhaust gas purification catalyst of scheme 1, the silica / alumina ratio (SAR) of the BEA type zeolite is 20 or more.
[0019] [Scheme 3] According to the exhaust purification catalyst of Scheme 1, the value of (A1+A2) / A0 is less than 0.47.
[0020] [Scheme 4] According to the exhaust purification catalyst of scheme 1, the full width at half maximum of the diffraction peak of 2θ=22.5±0.1° is less than 0.29°.
[0021] [Scheme 5] A method for producing an exhaust gas purification catalyst according to any one of schemes 1 to 4,
[0022] The method comprises calcining a BEA zeolite at a temperature of 650°C to 900°C, wherein the value of (A1+A2) / A0 of the BEA zeolite is 0.50 or more, and the full width at half maximum of the diffraction peak of 2θ=22.5±0.1° is 0.30° or less.
[0023] [Scheme 6] According to the method described in Scheme 5, the calcination temperature is higher than 700°C and lower than 800°C.
[0024] [Scheme 7] The method according to Scheme 5, wherein the moisture content in the atmosphere during the calcination at the calcination temperature is 1.00 volume % or less.
[0025] [Scheme 8] The method according to Scheme 5, wherein the moisture content in the atmosphere during the calcination at the calcination temperature is 0.80 volume % or less.
[0026] [Scheme 9] An exhaust gas purification catalyst device comprising a substrate and a catalyst coating on the substrate,
[0027] The catalyst coating layer includes the exhaust gas purification catalyst according to any one of aspects 1 to 4.
[0028] [Scheme 10] The exhaust gas purification catalyst device according to Scheme 9 is an under-floor catalyst.
[0029] [Scheme 11] An exhaust purification catalyst system comprises the exhaust purification catalyst device described in Scheme 9.
[0030] [Scheme 12] An exhaust purification method comprising: configuring the exhaust purification catalyst device described in Scheme 9 in the exhaust system of an internal combustion engine to purify the exhaust gas discharged from the internal combustion engine.
[0031] [Scheme 13] An exhaust purification method comprises: configuring the exhaust purification catalyst system described in Scheme 11 in the exhaust system of an internal combustion engine to purify the exhaust gas discharged from the internal combustion engine.
[0032] The exhaust gas purification catalyst of the present invention has few structural defects and excellent HC adsorption capacity in a cold state, and therefore can effectively reduce HC emissions in a cold region. DETAILED DESCRIPTION
[0033] 《Exhaust purification catalyst》
[0034] The exhaust gas purification catalyst of the present invention is an exhaust gas purification catalyst containing BEA type zeolite.
[0035] In FT-IR measurement using BEA type zeolite,
[0036] At 3730cm -1 Above and 3740cm -1 The following peak areas A1,
[0037] At 3720cm -1 Above and 3725cm -1 The following peaks have a peak area A2, and
[0038] In 1978cm -1 Above and 1983cm -1 The value of (A1+A2) / A0 calculated from the peak area A0 having the peak top is less than 0.50, and
[0039] The full width at half maximum of the diffraction peak at 2θ=22.5±0.1° in XRD measurement of the BEA-type zeolite is 0.30° or less.
[0040] The BEA type zeolite contained in the exhaust gas purification catalyst of the present invention has a value of (A1+A2) / A0 calculated using area A1, area A2 and area A0 in FT-IR measurement of less than 0.50. The BEA type zeolite in the exhaust gas purification catalyst of the present invention can be guaranteed to have a small amount of Si-OH groups accompanied by structural defects by this requirement.
[0041] In addition, the BEA zeolite contained in the exhaust gas purification catalyst of the present invention has a diffraction peak at 2θ=22.5±0.1° in XRD measurement with a full width at half maximum of 0.30° or less. The BEA zeolite in the exhaust gas purification catalyst of the present invention can be guaranteed to have a sufficiently maintained crystal structure by this requirement.
[0042] The BEA zeolite contained in the exhaust gas purification catalyst of the present invention is a BEA zeolite with few structural defects, as ensured by the above two requirements. Therefore, the exhaust gas purification catalyst of the present invention containing such a BEA zeolite has excellent HC adsorption capacity in a cold state, and if the exhaust gas purification catalyst device contains the catalyst, HC emissions in a cold state can be effectively reduced.
[0043] As described above, the BEA type zeolite contained in the exhaust gas purification catalyst of the present invention has a value of (A1+A2) / A0 calculated using the area A1, the area A2 and the area A0 in the FT-IR measurement, which is less than 0.50.
[0044] In the FT-IR measurement of BEA zeolite, at 3730 cm -1 Above and 3740cm -1 The peaks with peak tops below are considered to be from the stretching vibration of isolated Si-OH bonds. -1 Above and 3725cm -1 The peaks with the following peak tops are considered to be derived from the stretching vibration of the Si-OH bond to which hydrogen is bonded. -1 Above and 1983cm -1 The peaks with the following peak tops are considered to be derived from the stretching vibration of Si-O bonds.
[0045] Therefore, the value of the peak area ratio (A1+A2) / A0 of each peak in the FT-IR measurement of the BEA type zeolite is less than 0.50, which means that the ratio of Si-OH groups to Si-O bonds in the BEA type zeolite is small. Therefore, the BEA type zeolite having a value of (A1+A2) / A0 of less than 0.50 has a small amount of Si-OH groups associated with structural defects, so even in a cold state, the influence of adsorbed water adsorbed on Si-OH groups is small, and the expected HC adsorption capacity can be expressed.
[0046] The area ratio (A1+A2) / A0 of the BEA zeolite in the FT-IR measurement may be 0.48 or less, 0.47 or less, less than 0.47, 0.45 or less, 0.40 or less, or 0.35 or less. However, if the area ratio (A1+A2) / A0 is to be reduced beyond necessity, the calcination temperature during preparation needs to be increased, and there is a concern that the crystal structure of the BEA zeolite may be destroyed and the HC adsorption capacity may be impaired. From this viewpoint, the area ratio (A1+A2) / A0 may be 0.10 or more, 0.15 or more, 0.20 or more, 0.25 or more, or 0.30 or more.
[0047] The areas A1, A2 and A0 in the FT-IR measurement of the BEA-type zeolite can be quantified by peak fitting as described in the examples described later based on the obtained FT-IR spectrum.
[0048] The BEA zeolite contained in the exhaust gas purification catalyst of the present invention has a diffraction peak at 2θ=22.5±0.1° in XRD measurement with a full width at half maximum of 0.30° or less. The diffraction peak at 2θ=22.5±0.1° in XRD measurement is a characteristic peak of the BEA zeolite. When the full width at half maximum of the diffraction peak is 0.30° or less, it can be ensured that the BEA zeolite of the present invention is a zeolite with a fully developed BEA type crystal structure.
[0049] The full width at half maximum of the diffraction peak of 2θ=22.5±0.1° in the XRD measurement can be 0.29° or less, less than 0.29°, 0.28° or less, 0.26° or less, or 0.24° or less. On the other hand, even if the full width at half maximum of the diffraction peak of 2θ=22.5±0.1° is too narrow, the expected effect of the present invention will not increase inversely proportional thereto. Therefore, the full width at half maximum of the diffraction peak of 2θ=22.5±0.1° can be 0.10° or more, 0.15° or more, or 0.20° or more.
[0050] In order to ensure ease of synthesis, the silica / alumina ratio (SAR) of the BEA type zeolite contained in the exhaust gas purification catalyst of the present invention may be 20 or more, or may be 25 or more, 30 or more, 35 or more, or 40 or more. From the viewpoint of improving the adsorption capacity of HC, the SAR of the BEA type zeolite may be 100 or less, 80 or less, 60 or less, or 50 or less. The SAR is a value defined as the molar ratio of silica (SiO2) / alumina (Al2O3).
[0051] The BEA zeolite contained in the exhaust gas purification catalyst of the present invention may be chemically pure BEA zeolite, or may contain other components. Examples of other components include alkali metals, alkaline earth metals, rare earth metals, noble metals, and oxides thereof. Such other components may replace elements in the framework of the BEA zeolite, may be solid-dissolved with the BEA zeolite, or may be supported on the BEA zeolite.
[0052] The exhaust gas purification catalyst of the present invention includes the predetermined BEA type zeolite as described above. The exhaust gas purification catalyst of the present invention may also include components other than the predetermined BEA type zeolite. The components other than the BEA type zeolite contained in the exhaust gas purification catalyst of the present invention may be, for example, zeolites other than the BEA type zeolite, other inorganic oxides, etc.
[0053] The exhaust gas purification catalyst of the present invention may contain 70 mass % or more, 80 mass % or more, 85 mass % or more, 90 mass % or more, 95 mass % or more, 98 mass % or more, or 99 mass % or more of the predetermined BEA type zeolite relative to the total mass of the exhaust gas purification catalyst, or may contain 100 mass % of the predetermined BEA type zeolite.
[0054] The exhaust gas purification catalyst of the present invention may be in the form of particles. When the exhaust gas purification catalyst of the present invention is in the form of particles, its average particle size may be, for example, 0.1 μm or more, 0.5 μm or more, or 1.0 μm or more, and may be, for example, 500 μm or less, 300 μm or less, 100 μm or less, or 50 μm or less.
[0055] 《Method for manufacturing exhaust gas purification catalyst》
[0056] The exhaust gas purification catalyst of the present invention can be produced by various methods as long as it has the above-mentioned characteristics.
[0057] The exhaust gas purification catalyst of the present invention can be produced, for example, by the following method:
[0058] The method comprises calcining a BEA type zeolite (raw material zeolite) at a temperature of 650° C. or higher and 900° C. or lower.
[0059] The BEA-type zeolite has a peak area ratio (A1+A2) / A0 value of 0.50 or more in FT-IR measurement, and
[0060] The full width at half maximum of the diffraction peak at 2θ=22.5±0.1° in XRD measurement was 0.30° or less.
[0061] The raw material zeolite as above has the crystal structure of BEA type zeolite, but has more structural defects, so it is a zeolite with a high content of Si-OH groups. By calcining the raw material zeolite at above 650°C, dehydration of Si-OH groups is caused, Si-O-Si bonds are generated, and structural defects are repaired. In addition, by controlling the calcination temperature of the raw material zeolite to below 900°C, the crystal structure of the BEA type zeolite can be prevented from being destroyed by heat. The calcination temperature of the raw material zeolite can be above 670°C, above 700°C, above 720°C, or above 750°C, and can be below 880°C, below 850°C, below 830°C, or below 800°C.
[0062] Typically, the calcination temperature of the raw material zeolite may be, for example, 700° C. or higher and 800° C. or lower.
[0063] When the raw material zeolite is calcined, it is preferred that the moisture content in the surrounding atmosphere is small from the perspective of smooth dehydration of the Si-OH group of the raw material zeolite. From this viewpoint, it is preferred that the moisture content in the atmosphere at the calcination temperature during calcination is 10.0% by volume or less, 5.00% by volume or less, 3.00% by volume or less, 1.00% by volume or less, 0.90% by volume or less, 0.80% by volume or less, 0.60% by volume or less, 0.40% by volume or less, or 0% by volume.
[0064] The calcination time of the raw zeolite can be more than 10 minutes, more than 30 minutes, more than 60 minutes, more than 90 minutes, more than 120 minutes, more than 15 minutes, more than 180 minutes, more than 210 minutes, more than 240 minutes or more than 270 minutes, and can be less than 1500 minutes, less than 1000 minutes, less than 720 minutes, less than 660 minutes, less than 600 minutes, less than 540 minutes, less than 480 minutes or less than 420 minutes.
[0065] The exhaust gas purification catalyst of the present invention can be produced, for example, as described above. The exhaust gas purification catalyst of the present invention can be used after being crushed and classified as necessary.
[0066] 《Exhaust purification catalyst device》
[0067] According to another aspect of the present invention, an exhaust gas purification catalyst device is provided.
[0068] The exhaust gas purification catalyst device of the present invention is an exhaust gas purification catalyst device having a substrate and a catalyst coating layer on the substrate.
[0069] The catalyst coating layer contains the exhaust gas purification catalyst of the present invention.
[0070] <Base Material>
[0071] The substrate can be appropriately selected from substrates known as substrates for exhaust gas purification catalyst devices. For example, a straight-flow type or wall-flow type monolithic honeycomb substrate made of a material such as cordierite, SiC, stainless steel, or inorganic oxide particles can be used.
[0072] <Coating>
[0073] The coating layer of the exhaust gas purification catalyst device of the present invention contains the exhaust gas purification catalyst of the present invention.
[0074] The coating of the exhaust gas purification catalyst device of the present invention may contain other optional components as required in addition to the exhaust gas purification catalyst of the present invention. The optional components may be, for example, inorganic oxides, precious metals, adhesives, etc. Inorganic oxides may be, for example, oxides of silicon dioxide, aluminum oxide, zirconium dioxide, titanium dioxide, rare earth elements, etc., and composite oxides containing two or more of them. The precious metal may be a platinum group metal, for example, one or more selected from platinum, palladium, rhodium, etc. The adhesive may be selected, for example, from alumina sol, titanium dioxide sol, etc.
[0075] The coating of the exhaust gas purification catalyst device of the present invention may be a coating of a single-layer structure consisting only of a coating containing the exhaust gas purification catalyst of the present invention, may be a coating of a laminated structure containing two or more layers of coatings containing the exhaust gas purification catalyst of the present invention, or may be a coating of a laminated structure having one or more layers of coatings containing the exhaust gas purification catalyst of the present invention and further having other coatings. For example, the other coatings may be optional coatings containing inorganic oxides, precious metals, adhesives, etc.
[0076] The exhaust gas purification catalyst device of the present invention preferably contains a certain amount of the predetermined BEA type zeolite of the present invention. In the exhaust gas purification catalyst device of the present invention, the amount of the BEA type zeolite per 1L of substrate capacity may be, for example, 1 g / L or more, 5 g / L or more, 10 g / L or more, 15 g / L or more, or 20 g / L or more, and may be, for example, 200 g / L or less, 150 g / L or less, 100 g / L or less, 80 g / L or less, 60 g / L or less, 50 g / L or less, or 40 g / L or less.
[0077] <Purpose>
[0078] The exhaust gas purification catalyst device of the present invention can be used as, for example, an exhaust gas purification device of equipment including an internal combustion engine (tools, generators, high-pressure cleaners, etc.), an underfloor catalyst device of an automobile including an internal combustion engine, etc.
[0079] 《Exhaust purification catalyst system》
[0080] According to still another aspect of the present invention, an exhaust gas purification catalyst system is provided.
[0081] The exhaust gas purification catalyst system of the present invention includes the exhaust gas purification catalyst device of the present invention.
[0082] The exhaust gas purification catalyst system of the present invention may be, for example, a system including a starting catalyst device and the exhaust gas purification catalyst device of the present invention as an underfloor catalyst device. The starting catalyst device may be appropriately selected from known starting catalyst devices for automobiles including internal combustion engines.
[0083] 《Exhaust gas purification method》
[0084] According to another aspect of the present invention, an exhaust gas purification method is provided.
[0085] As the exhaust gas purification method of the present invention, for example, the following steps and the like can be exemplified as embodiments:
[0086] The exhaust gas purification catalyst device of the present invention is arranged in the exhaust system of the internal combustion engine to purify the exhaust gas discharged from the internal combustion engine;
[0087] The exhaust gas purification catalyst system described in the present invention is disposed in an exhaust system of an internal combustion engine to purify exhaust gas exhausted from the internal combustion engine.
[0088] Example
[0089] 《Examples 1 to 9 and Comparative Examples 1 to 5》
[0090] In Examples 1 to 9 and Comparative Examples 1 to 5, the SiOH content of zeolite, the half maximum width of the diffraction peak derived from BEA zeolite, and the amount of decane adsorbed in the presence of water were investigated according to the calcination conditions. The SiOH content of zeolite and the half maximum width of the diffraction peak were measured as follows.
[0091] 1. SiOH content of zeolite
[0092] The SiOH content of zeolite was measured using FT-IR in accordance with JIS K0117:2017 (General Rules for Infrared Spectroscopic Analysis) in the following procedure.
[0093] The zeolite sample obtained in each example or comparative example was pulverized in a mortar. 10 mg of the pulverized product was compression-molded under a pressure of 10 MPa to prepare a disk-shaped sample with a diameter of 10 mm. The obtained disk-shaped sample was subjected to FT-IR measurement under the following conditions.
[0094] Measuring device: JASCO Corporation, Fourier transform infrared spectrophotometer, "FT / IR-6600"
[0095] Measurement method: transmission method
[0096] Measurement wavelength range: 4000~1000cm -1
[0097] Resolution: 4cm -1
[0098] Detector: Medium-band Mercury Cadmium Telluride (MCT) detector
[0099] Total times: 64 times
[0100] Measuring temperature: 500℃
[0101] Measurement atmosphere: 10 volume % -O2 / N2 flow
[0102] Regarding the spectrum of zeolite, the above-mentioned disk sample was loaded into the sample chamber of the measuring device, and the temperature was increased from room temperature to 500°C at a rate of 20°C / min under a 10 vol%-O2 / N2 flow, and the temperature was maintained at 500°C for 10 minutes before measurement.
[0103] The background spectrum was measured in the same manner as the spectrum of zeolite, except that an empty cell was placed in the sample chamber instead of the disk-shaped sample.
[0104] The FT-IR spectrum of the obtained zeolite was analyzed as follows by subtracting the background spectrum from the spectrum of the sample using the analysis software "JASCO SpectraManager Ver.2" manufactured by JASCO Corporation.
[0105] (1) Calculation of peak areas (A1, A2) derived from SiOH
[0106] By connecting the wave number 4000cm with a straight line -1 Absorbance and wave number 3000cm -1 The absorbance was corrected between two points and the baseline was set. -1The spectrum of the range was fitted with the peaks of peak numbers 1 to 5 described in Table 1. In addition, the area A1 of the peak number 1 and the area A2 of the peak number 2 were defined as the amount of SiOH on the outer surface of the zeolite and the amount of SiOH on the inner surface of the zeolite, respectively. The fitting was performed with reference to the non-patent document "Materials Today: Proceedings 42 (2021) pp211-216".
[0107] Table 1
[0108]
[0109] (2) Calculation of the peak area A0 from SiO
[0110] By at wave number 2120cm -1 The baseline is set by a single-point calibration of the absorbance at . -1 The spectrum of the range of , was fitted with the peaks of peak numbers 1 to 3 described in Table 2. And the area A0 of the peak of peak number 1 was defined as the SiO content of the zeolite. This fitting was performed with reference to the non-patent document "Applied Catalysis A: General 200 (2000) pp125-134".
[0111] Table 2
[0112]
[0113] (3) Calculation of the amount of SiOH contained in the zeolite sample
[0114] The amount of SiOH contained in the framework (SiO) of zeolite (the total amount of SiOH on the outer surface and the amount of SiOH on the inner surface) was calculated by the following formula.
[0115] SiOH amount = (A1 + A2) / A0
[0116] 2. Full width at half maximum of the diffraction peak from BEA zeolite
[0117] The full width at half maximum of the diffraction peak derived from the BEA-type zeolite is determined by the method described below from the results of X-ray diffraction (XRD) measured under the following conditions in accordance with JIS K0131:1996 (General Rules for X-ray Diffraction Analysis).
[0118] Measurement equipment: X-ray diffraction equipment, "RINT-TTR III" manufactured by Rigaku Co., Ltd.
[0119] Scan axis: 2θ / θ
[0120] Radiation source: CuK α
[0121] Measurement method: continuous
[0122] Voltage: 40kV
[0123] Current: 250mA
[0124] Measuring range: 2θ = 5 to 85°
[0125] Sampling amplitude: 0.02°
[0126] Scanning speed: 8.00° / min
[0127] Divergence slit: 1°
[0128] Divergence longitudinal limiting slit: 10mm
[0129] Scattering slit: 8mm
[0130] Light receiving slit: 13mm
[0131] The obtained XRD pattern was subjected to data processing under the following conditions using comprehensive powder X-ray analysis software "PDXL2" manufactured by Rigaku Corporation.
[0132] Data processing mode: automatic
[0133] Peak search conditions
[0134] σ cutoff value: 3.00
[0135] σ cut-off range: 0.50~20.00
[0136] Among the obtained peaks, the peak with a peak top of 2θ=22.5±0.1° was defined as a diffraction peak derived from the BEA-type zeolite, and its full width at half maximum was calculated.
[0137] 3. Decane adsorption in the presence of water
[0138] The zeolite samples obtained in each example or comparative example were examined for the amount of decane adsorption in the presence of water according to the following procedure.
[0139] The zeolite sample was ground in a mortar. 3.0 g of the ground material was compressed and molded at a pressure of 26 MPa for 1 minute to produce a disk sample with a diameter of 35 mm. The obtained disk sample was coarsely ground in a mortar and then classified to obtain a tablet sample with a size of 0.5 to 1.0 mm.
[0140] The tablet sample was placed in a dryer at 250°C for 30 minutes to obtain a dried tablet sample. A tablet sample with a dry mass of 0.5 g was loaded into an adsorption device (catalyst evaluation device "SIGU-1000" manufactured by Horiba, Ltd.), and the temperature was raised from room temperature to 500°C at a rate of 25°C / min under a 10 volume %-O2 / N2 flow, and maintained at 500°C for 10 minutes. In this way, a pretreatment was performed to remove hydrocarbons and water remaining in the pores of the zeolite sample. After the sample temperature was lowered to 100°C, a decane-containing simulated gas of the following composition was circulated in the adsorption device at a flow rate of 5L / min for 15 minutes to adsorb decane to the zeolite sample. The gas concentration at this time was measured using the FTIR method engine exhaust measurement device "MEXA-ONE-FT" manufactured by Horiba, Ltd.
[0141] Decane: 3000ppm-C (3000ppm based on carbon mass)
[0142] Water: 3% by volume
[0143] Nitrogen: Balance
[0144] After the simulated gas containing decane was circulated for 15 minutes, the circulating gas was switched to 100% nitrogen and maintained at 100°C for 5 minutes. Thereafter, the sample temperature was raised to 550°C at a heating rate of 20°C / min while the nitrogen flow was maintained, so that decane was desorbed from the zeolite sample. The cumulative amount of desorbed decane was taken as the decane adsorption amount (mg / g-zeolite) in the presence of water.
[0145] <Example 1>
[0146] As a raw material, a commercially available BEA type zeolite (manufactured by Tosoh Corporation, high silica zeolite "HSZ-940HOA" SiO2 / Al2O3 (SAR) = 40) was used, and it was calcined at 700°C for 300 minutes under atmospheric pressure. The calcination was carried out by using an electric furnace, heating from room temperature to a target temperature (700°C) at a heating rate of 25°C / min under atmospheric pressure, and maintaining the target temperature for 300 minutes. Thereafter, the heater of the electric furnace was turned off, and the sample was cooled to room temperature in the electric furnace. The H2O concentration of the calcination atmosphere at the target temperature (700°C) was 0.90% by volume.
[0147] The above-mentioned measurements were performed on the obtained calcined zeolite. The results are shown in Table 3.
[0148] <Examples 2 to 9 and Comparative Examples 1 to 5>
[0149] Zeolite samples were obtained by calcining in the same manner as in Example 1 except that the calcining conditions were changed as shown in Table 3. The above-mentioned various measurements were performed on the obtained zeolite samples.
[0150] In Comparative Example 1, the raw material BEA type zeolite was not calcined and was provided as it was for various measurements. In Example 2, calcination was performed in an atmosphere consisting of 20 volume % oxygen and 80 volume % nitrogen. In Examples 3 to 6, calcination was performed in an atmosphere in which the H2O concentration was adjusted to the concentration shown in Table 3 by mixing a mixed gas consisting of 20 volume % oxygen and 80 volume % nitrogen and a humidified atmosphere having a moisture content (H2O concentration) of 10 volume % at the calcination temperature in a predetermined ratio. In Example 8, calcination was performed in a humidified atmosphere having a moisture content (H2O concentration) of 10 volume % at the calcination temperature.
[0151] Furthermore, in the XRD analysis of the zeolite sample of Comparative Example 5, no diffraction peak at 2θ=22.5±0.1° was detected.
[0152] The results are shown in Table 3.
[0153]
[0154] The following can be understood from Table 3.
[0155] The samples of Comparative Example 1 in which the raw material BEA zeolite was not calcined, and Comparative Examples 2 and 3 in which the calcination temperature was lower than 650°C, had a full width at half maximum of 0.30 or less at the peak of 2θ=22.5±0.1° in XRD, and the crystal structure of the BEA zeolite was maintained, and the SiOH content was as high as 0.50 or more. The decane adsorption amount in the presence of water for these samples was low.
[0156] On the other hand, the samples of Comparative Examples 4 and 5, in which the raw material BEA-type zeolite was calcined at a temperature exceeding 900°C, had a low SiOH content of less than 0.50, but the full width at half maximum of the peak at 2θ=22.5±0.1° in XRD exceeded 0.30, or the peak at 2θ=22.5±0.1° was not detected, indicating that the crystal structure of the BEA-type zeolite was destroyed. The decane adsorption amount in the presence of water for these samples was extremely low. This is considered to be because the pore structure of the BEA-type zeolite was destroyed, and thus decane could not be adsorbed.
[0157] In contrast, the samples of Examples 1 to 9, in which the raw material BEA zeolite was calcined at a temperature of 650 to 900°C, had a full width at half maximum of less than 0.29 at the peak of 2θ=22.5±0.1° in XRD, which maintained the crystal structure of the BEA zeolite, and a low SiOH content of less than 0.50. The decane adsorption in the presence of water for these samples showed high values. In addition, the following tendency can be seen from the comparison of Examples 2 to 8: when the calcination temperature is the same, the less the moisture content (H2O concentration) in the atmosphere during calcination, the greater the decane adsorption in the presence of water.
[0158] 《Real car evaluation》
[0159] The zeolite samples obtained in Examples 2 and 7 and Comparative Example 1 were used to investigate the HC emission in an actual vehicle evaluation, thereby verifying the effect of the exhaust gas purification catalyst system including the exhaust gas purification catalyst of the present invention.
[0160] The exhaust gas purification catalyst system includes a starting catalyst device and an under-floor catalyst device.
[0161] The starter catalyst device has a catalyst coating layer (lower layer) containing Pd and a catalyst coating layer (upper layer) containing Rh formed in sequence on a straight honeycomb substrate made of cordierite.
[0162] The under-floor catalyst device sequentially forms a catalyst coating (lower layer) containing the zeolite sample of Example 2 or 7, or Comparative Example 1, a catalyst coating (middle layer) containing Pd, and a catalyst coating (upper layer) containing Rh on the same honeycomb substrate as above.
[0163] In addition, as Comparative Example 6, an exhaust gas purification catalyst system including the above-mentioned starting catalyst device and the below-mentioned underfloor catalyst device was used to conduct an actual vehicle evaluation.
[0164] The under-floor catalyst device has a catalyst coating layer (lower layer) containing Pd and a catalyst coating layer (upper layer) containing Rh formed in sequence on a honeycomb substrate.
[0165] Each of the above exhaust purification catalyst systems was installed in a gasoline engine vehicle with an exhaust volume of 1500cc, and a total hydrocarbon (THC) concentration measuring device was installed on the outlet side of the underfloor catalyst device. The vehicle was operated in the WLTC mode on a chassis dynamometer, and the cumulative emission of THC at a low power factor (0 to 600 seconds in the WLTC mode) was calculated as the HC emission in the cold region (mg / km). The results are shown in Table 4.
[0166] Table 4
[0167]
[0168] The HC emission in the cold zone of the exhaust gas purification catalyst system of Comparative Example 6 using the underfloor catalyst device having no catalyst coating layer containing zeolite was 16.81 mg / km.
[0169] On the other hand, the HC emission of the exhaust gas purification catalyst system using the underfloor catalyst device having the catalyst coating layer containing the zeolite of Comparative Example 1 which does not satisfy the provisions of the present invention is 14.16 mg / km. That is, the reduction amount of HC emission of the underfloor catalyst device of the exhaust gas purification catalyst system of Comparative Example 1 is improved by 2.65 mg / km (16.81-14.16=2.65 (mg / km)) compared with the underfloor catalyst device of Comparative Example 6.
[0170] In contrast, the HC emission of the exhaust gas purification catalyst system using the underfloor catalyst device having the catalyst coating containing the zeolite of Examples 2 and 7 satisfying the requirements of the present invention was 13.00 mg / km in Example 2 and 13.26 mg / km in Example 7. That is, compared with the underfloor catalyst device of Comparative Example 6,
[0171] The reduction in HC emissions of the underfloor catalyst device having a catalyst coating comprising the zeolite of Example 2 was 3.81 mg / km (=16.81-13.00=3.81 (mg / km)),
[0172] The HC emission reduction of the underfloor catalyst device having the catalyst coating layer comprising the zeolite of Example 7 was 3.55 mg / km (=16.81-13.26=3.55 (mg / km)).
[0173] Therefore, it can be seen that by using the zeolites of Examples 2 and 7 satisfying the requirements of the present invention, HC emissions are greatly improved compared to the case where the zeolite of Comparative Example 1 not satisfying the requirements of the present invention is used. Regarding the improvement rate of HC emissions,
[0174] In Example 2, it is 43.8% ({3.81-2.65} / 2.65}×100=43.8(%)),
[0175] In Example 7, it is 34.0% ({3.55-2.65) / 2.65}×100=34.0(%)).
[0176] From the results of Table 4, it was verified that the exhaust gas purification catalyst system including the exhaust gas purification catalyst of the present invention is effective in reducing the HC emission amount in the cold region.
Claims
1. An exhaust gas purification catalyst comprising BEA type zeolite, In the FT-IR measurement using the BEA-type zeolite, At 3730cm -1 Above and 3740cm -1 The following peak areas A1, At 3720cm -1 Above and 3725cm -1 The following peaks have a peak area A2, and In 1978cm -1 Above and 1983cm -1 The value of (A1+A2) / A0 calculated from the peak area A0 having the peak top is less than 0.50, and The full width at half maximum of a diffraction peak at 2θ=22.5±0.1° in XRD measurement of the BEA-type zeolite is 0.30° or less. 2 . The exhaust gas purification catalyst according to claim 1 , wherein the BEA type zeolite has a silica / alumina ratio (SAR) of 20 or more. 3 . The exhaust gas purification catalyst according to claim 1 , wherein the value of ( A1 + A2 ) / A0 is less than 0.
47. 4 . The exhaust gas purification catalyst according to claim 1 , wherein the full width at half maximum of the diffraction peak at 2θ=22.5±0.1° is less than 0.29°.
5. A method for producing an exhaust gas purification catalyst according to any one of claims 1 to 4, The method comprises calcining a BEA zeolite at a temperature of 650°C to 900°C, wherein the value of (A1+A2) / A0 of the BEA zeolite is 0.50 or more, and the full width at half maximum of the diffraction peak of 2θ=22.5±0.1° is 0.30° or less. The method according to claim 5 , wherein the calcination temperature is 700° C. or higher and 800° C. or lower. 7 . The method according to claim 5 , wherein the moisture content in the atmosphere during the calcination at the calcination temperature is 1.00% by volume or less. 8 . The method according to claim 5 , wherein the amount of water in the atmosphere during the calcination at the calcination temperature is 0.80% by volume or less.
9. An exhaust gas purification catalyst device comprising a substrate and a catalyst coating on the substrate, The catalyst coating layer includes the exhaust gas purification catalyst according to any one of claims 1 to 4.
10. The exhaust gas purification catalyst device according to claim 9, which is an underfloor catalyst.
11. An exhaust gas purification catalyst system comprising the exhaust gas purification catalyst device according to claim 9.
12. An exhaust gas purification method, comprising: arranging the exhaust gas purification catalyst device according to claim 9 in an exhaust system of an internal combustion engine, and purifying exhaust gas exhausted from the internal combustion engine.
13. An exhaust gas purification method, comprising: disposing the exhaust gas purification catalyst system according to claim 11 in an exhaust system of an internal combustion engine, and purifying exhaust gas exhausted from the internal combustion engine.
Citation Information
Patent Citations
Hydrocarbon adsorbent, exhaust gas-cleaning catalyst and exhaust gas cleaning method
JP2007275877A